ANTHROPOMETRIC PROFILE OF AGED PRACTITIONERS OF PHYSICAL ACTIVITY (Fiep Bulletin - online, 2014)
Introduction: The excess of weight and/or accumulation of corporal fat are considered factors of risks for the development of illnesses. Objective: To verify the BMI of participant men of the Project Dances Folkloric and Gymnastic for Third Age of the CDS/UFSC, by means of the classifications of the World-wide Health Organization (WHO) and American Pan Organization of Health (APOH). Methodology: The sample was composed for 48 men, with age enters the 60 and 90 years (x 71,2 years; ±7, 8). The anthropometrics data of corporal mass and stature had been collected in março/2006. One used the points of cut recommended by WHO (1997) and APOH (1997). The analysis was of the descriptive type, by means of frequency and percentage. Results: In accordance with the classification of the WHO, the majority of the aged ones (54,2%) are classified with overweight, having been the age groups of 65-69 years the one that presented greater percentage (50%) and 29.2% are with normal weight. Already according to APOH 16.7% is with overweight; 50% meet with the normal weight, being age group 65-69 years with percentile greater (22, 9%). However 18.8% are with low weight and 14.6% are classified in obese. Conclusion: The results suggest that it has difference between the classifications, especially between normal weight and overweight. Although the two indicate a significant obesity and aged classifications number with overweight. However the classification proposal for the APOH is specific for aged, being higher the cut points, while for the WHO the values are equal for all the age group. In this way it is indicated classification for the APOH for this age group, exactly that this is not specific for the Brazilian population.
Keywords: BMI; aged physical activity